2014
DOI: 10.1002/ajmg.a.36678
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing identifies three novel mutations in ANTXR1 in families with GAPO syndrome

Abstract: GAPO syndrome (OMIM#230740) is the acronym for growth retardation, alopecia, pseudoanodontia, and optic atrophy. About 35 cases have been reported, making it among one of the rarest recessive conditions. Distinctive craniofacial features including alopecia, rarefaction of eyebrows and eyelashes, frontal bossing, high forehead, mid-facial hypoplasia, hypertelorism, and thickened eyelids and lips make GAPO syndrome a clinically recognizable phenotype. While this genomic study was in progress mutations in ANTXR1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Of these four variants, ANTXR1 was considered the strongest candidate for pathogenicity based on amino acid conservation, predictions of deleteriousness, and minor allele frequencies in the ExAC databases (in which only the ANTXR1 variant was not observed in homozygosity). Prior reports of ANTXR1 in association with pseudoanodontia provided additional evidence supporting the potential involvement of ANTXR1 in tooth development [Bayram et al 2014; Stranecky et al 2013]. Segregation analysis was performed on the ANTXR1 and KDM2B variants, and only the variant in ANTXR1 followed the expected mode of inheritance (Fig.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Of these four variants, ANTXR1 was considered the strongest candidate for pathogenicity based on amino acid conservation, predictions of deleteriousness, and minor allele frequencies in the ExAC databases (in which only the ANTXR1 variant was not observed in homozygosity). Prior reports of ANTXR1 in association with pseudoanodontia provided additional evidence supporting the potential involvement of ANTXR1 in tooth development [Bayram et al 2014; Stranecky et al 2013]. Segregation analysis was performed on the ANTXR1 and KDM2B variants, and only the variant in ANTXR1 followed the expected mode of inheritance (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…To date, nine different biallelic ANTXR1 variants have been suggested as etiologic for GAPO syndrome [Bayram et al 2014; Benetti-Pinto et al 2016; Chattopadhyay et al 2017; Salas-Alanis et al 2016; Stranecky et al 2013] (Fig. 2c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homozygous ANTXR1 loss-of-function mutations cause growth retardation, alopecia, pseudo-anodontia and optic atrophy in GAPO patients [2, 14]. Additional GAPO features include prominent scalp veins, hemangioma-like vascular anomalies, and progressive skin fibrosis [3, 15].…”
Section: Introductionmentioning
confidence: 99%
“…They also analyzed the loss of function of these variants using fibroblasts isolated from the patients. Later, Bayram et al [2014] analyzed 5 GAPO patients from 3 unrelated Turkish families by exome sequencing, describing the presence of an indel mutation that produces a truncated protein, a missense mutation predicted to be a deleterious version of the protein, and a synonymous mutation that seems to modify a splicing site in ANTXR1 . In our study, we identified a new missense mutation (c.410A>T, Q137L) in the ANTXR1 gene in a Mexican family.…”
mentioning
confidence: 99%